(untitled) (Journal of Forestry, 2024)
Evapotranspiration is an important part of the hydrological water cycle as well as an important component in irrigation planning and drought determination. The aim of this research is to compare the amounts of potential evapotranspiration according to different methods in different climate types as well as the correlation between them. Potential evapotranspiration (in mm) was calculated according to Thornthwaite, Ivanov, Blaney-Criddle and Penman-Monteith methods for Osijek, Zagreb-Maksimir, Parg, Zavižan and Hvar weather stations. Osijek weather station has a Cfa climate type, a moderately warm rainy climate with hot summers. Zagreb-Maksimir and Parg weather stations have Cfb climate type, moderately warm humid climate with hot summers. Zavižan weather station has Df climate type, humid boreal climate, while Hvar weather station is located in the area of Mediterranean climate with hot summers (Csa climate type). In the area of lowland Croatia in Cfa and Cfb climate types, the average amount of potential evapotranspiration was the lowest according to the Blaney- Criddle method (709.30 mm), and the highest according to the Ivanov method (859.95 mm). For Parg weather station in mountainous Croatia, Cfb climate type, the lowest average amount of potential evapotranspiration was found according to the Ivanov method (553.01 mm), while in this case the highest amount was found according to the Penman-Monteith method (705.87 mm). On Hvar, Csa type climate, the smallest amount of potential evapotranspiration was recorded according to the Thornthwaite method (891.57 mm), and the largest according to the Ivanov method in the amount of 1368.55 mm. According to the average annual values of potential evapotranspiration, the Penman- Monteith method was the closest to the Ivanov method in the area of lowland Croatia, and the Blaney- Criddle method in the area of mountainous, sub-mountainous and Mediterranean Croatia. The highest correlation in the amount of r = 0.98* was between the Thornthwaite and Blaney-Criddle methods, and the smallest in the amount of r = 0.49* was determined between the Ivanov and Blaney-Criddle methods. The Pennman-Monteith, Thornthwaite and Ivanov methods in lowland Croatia, and Thornthwaite and Blaney-Criddle methods in mountainous, pre-mountainous and Mediterranean Croatia had the highest correlation.